2005
DOI: 10.1177/153537020523000807
|View full text |Cite
|
Sign up to set email alerts
|

Phytoestrogens Induce Differential Estrogen Receptor Alpha- or Beta-Mediated Responses in Transfected Breast Cancer Cells

Abstract: Increased intake of phytoestrogens may be associated with a lower risk of cancer in the breast and several other sites, although there is controversy surrounding this activity. One of the mechanisms proposed to explain the activity of phytoestrogens is their ability to bind and activate human estrogen receptor alpha (ERalpha) and human estrogen receptor beta (ERbeta). Nine phytoestrogens were tested for their ability to transactivate ERalpha or ERbeta at a range of doses. Mammary adenocarcinoma (MCF-7) cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
152
4
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(172 citation statements)
references
References 74 publications
14
152
4
2
Order By: Relevance
“…It has been shown that ERK induces the AP-1 activation (Karin, 1995), thus kaempferol may promote the ALP activity in UMR-106 cells through similar mechanism. In the presence of ER, kaempferol activated AP-1 more potently than quercetin, which well resembles other finding that kaempferol antagonizes estradiol more potently than quercetin (Zava et al, 1997;Harris et al, 2005). Interestingly, isorhamnetin exhibited inhibitory effect on AP-1 activation in the presence of ER subtypes, suggesting its action may be different with quercetin or kaempferol.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…It has been shown that ERK induces the AP-1 activation (Karin, 1995), thus kaempferol may promote the ALP activity in UMR-106 cells through similar mechanism. In the presence of ER, kaempferol activated AP-1 more potently than quercetin, which well resembles other finding that kaempferol antagonizes estradiol more potently than quercetin (Zava et al, 1997;Harris et al, 2005). Interestingly, isorhamnetin exhibited inhibitory effect on AP-1 activation in the presence of ER subtypes, suggesting its action may be different with quercetin or kaempferol.…”
Section: Discussionsupporting
confidence: 84%
“…Quercetin and kaempferol activated AP-1 reporter by both ER␣ and ER␤, which makes them behave more like ER antagonists. This further demonstrated previous observation that kaempferol and quercetin antagonized 17␤-estradiol, and kaempferol was more potent than quercetin (Zava et al, 1997;Harris et al, 2005). Contrary to quercetin and kaempferol, isorhamnetin (10-50 M) inhibited AP-1 reporter expression in the presence of ER␣ or ER␤.…”
Section: Selective Estrogen Receptor Antagonist Activitysupporting
confidence: 89%
“…We extensively investigated the effects of various steroidal compounds on the transcriptional regulation by Tip60. Consistent with the previous findings (36,60,61), we found that estrogenic compounds (E 2 and DPN) and phytoestrogens (GEN, EQ, DAI, and API) up-regulated ER␤1 transactivation at ERE, whereas SERMs (TAM and RAL) and antiestrogen (ICI) did the opposite. Surprisingly, DPN, GEN, and EQ abolished Tip60-mediated inhibition at the ERE site.…”
Section: Discussionsupporting
confidence: 81%
“…Estrogenic activity of equol has been identified by others in cultured human cells (12,13) and in healthy humans (14). Equol has been shown to bind to both estrogen receptor (ER) ␣ and ER-␤ and to effectively activate both receptors, although with greater transactivation of ER-␤ (13,15). Furthermore, antioxidant response elements associated with the ERs have been described (16), so that the antioxidant and estrogenic properties of equol might be functionally linked.…”
mentioning
confidence: 99%